Sleeping late is a risk factor for myopia development amongst school-aged children in China - Liu, Xiao Nicole; Naduvilath, Thomas John; Wang, Jingjing; Xiong, Shuyu; He, Xiangui; Xu, Xun; Sankaridurg, Padmaja R. (Scientific reports, 2020)
Myopia, a leading cause of distance vision impairment, is projected to affect half of the world’s population in 30 years. We analysed the relationship between certain demographic, environmental, and behavioural factors and myopia from a 2-year school-based, prospective trial conducted in Shanghai, China. This trial enrolled 6295 school-aged children at baseline and followed them up for 24 months. The relationship between abovementioned factors and myopia was examined and the role of sleep in childhood myopia development was highlighted. Our results suggest that ‘sleeping late’ is a risk factor for myopia prevalence at baseline (odds ratio [OR] = 1.55, p = 0.04), 2-year myopia incidence (odds ratio [OR] = 1.44, p = 0.02) and progression over 24 months ( p = 0.005), after adjusting for residency area, age, gender, sleep duration, and time spent outdoors. The identification and consistency of results with late sleepers being a susceptible group to both myopia onset and progression suggests a complex relationship between circadian rhythm, indoor environment, habitual indoor activities and myopia development and progression. These results can offer new insights to future myopia aetiology studies as well as aid in decision-making of myopia prevention strategies.